2021
DOI: 10.7759/cureus.13591
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Blood Loss Improves Detection of Postpartum Hemorrhage and Accuracy of Postpartum Hemorrhage Rates: A Retrospective Cohort Study

Abstract: Objective To evaluate the ability of estimated blood loss (EBL) and quantitative blood loss (QBL) to predict the need for blood transfusion in postpartum patients. Methods This is a retrospective observational study involving all deliveries one year before and after the change from EBL to QBL assessment in June 2017. Blood loss, need for blood transfusion, admission hematocrit, and postpartum nadir hematocrit were collected. Descriptive and bivariable analyses were performed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Estimated blood loss is less reliable than quantitative blood loss assessment and likely underestimates total blood loss volume. 24 Similarly, institutional protocols for ICU admission and transfusion likely varied. Missing data are a challenge with all real-world data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated blood loss is less reliable than quantitative blood loss assessment and likely underestimates total blood loss volume. 24 Similarly, institutional protocols for ICU admission and transfusion likely varied. Missing data are a challenge with all real-world data collection.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Blosser et al showed QBL is a more sensitive test for detecting clinically significant blood loss that could lead to an earlier diagnosis and treatment of PPH. 16 In our study, we directly measured blood loss with QBL. 17 To our knowledge, only one other study has used QBL and the authors just found an association between antenatal mean platelet volume and platelet distribution width values (i.e., not platelet count) and blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we did not have information about the emergent nature of cesarean births, which could predict heightened perception of trauma (Burcher et al 2020;Stoll et al 2018;Wada et al 2019). Fifth, medical record data were entered by multiple physicians, nurse practitioners, or certified nurse midwifes, with the potential for inaccuracy, particularly in estimating blood loss (Blosser et al 2021). Future efforts that use formal quantification methods are warranted to generate more precise blood loss estimates that are associated with increased risk for trauma and/or PPD (Blosser et al 2021).…”
Section: Discussionmentioning
confidence: 99%